The Competition Law Institutions in the BRICS Countries Need Better Enforcement Mechanisms - N. Kumar (BRICS Law Journal, 2025)
This study emphasizes the need for improved enforcement mechanisms within the competition law institutions of the BRICS countries, as these mechanisms play a vital role in ensuring fair competition and preventing anti-competitive behavior in their respective economies. The shifting trend of the digital market invites many challenges in the current enforcement mechanisms, particularly in India. For that purpose, a close examination of the institutional frameworks and enforcement mechanisms of competition law is required. This article starts with a brief introduction, highlighting the significance of the international competition law agenda and the BRICS countries. It also focuses on the evolution of institutional growth and the efforts undertaken by the respective national competition law authorities in the BRICS countries to improve their enforcement process not only during the COVID-19 pandemic but also to meet other upcoming challenges. Further, it examines whether these nations, including India, have adequately developed enforcement mechanisms or if they require more attention in order to effectively regulate. The results of this study reveal that the competition law agencies in BRICS have made tremendous efforts in this area, especially during the COVID-19 pandemic, and highlight a trending change in their enforcement mechanisms onto digital platforms. However, there are certain important areas where these nations need to improve their institutional framework, regulatory mechanisms, enforcement process, and other aspects. In the end, the author suggests some recommendations for policy-making and future implementations